(untitled) (Research, Society and Development, 2020)
Objective: To identify the main adverse effects caused by chemotherapeutic agents used in the treatment of cancer and how the nursing professional can act to alleviate such complications. Methodology: This is an integrative literature review and aims to identify the main adverse effects caused by chemotherapeutic agents used in the treatment of cancer and how the nursing professional can act to alleviate such complications. The databases LILACS, Portal Periódicos CAPES and SciELO were used, using the descriptors: Nursing; Oncology; Chemotherapy. The sample was selected in September 2020 and the period for selection was articles published between 2014 and August 2020, with 10 articles for the final sample. Results and discussions: Studies show that about 40% of patients using chemotherapy drugs have oral complications, where mucositis is the most frequent, although it presents in varying degrees. Such effects can occur during treatment or even seven after the drug is discontinued. Final considerations: Many nursing care procedures were mentioned by the authors of the sample, with guidance on possible complications being highly emphasized, in addition to assessing the patient’s condition. However, in order for nursing professionals to provide pertinent clarifications, it is necessary that they are trained to perform such a task.